Pengaruh Duta Merek terhadap Citra Merek L'Oreal Paris - Samantha Alicia; Leonnard Ong (STARKI, 2021)
Along with the times, cosmetics and beauty industries in the world are increasingly developing and innovating, including in Indonesia. Various global cosmetics brands enter the Indonesian market. In intense competition, it is very important to build a good brand image. Various communication strategies are carried out, one of them is by using brand ambassadors. L'Oreal Paris is one of the cosmetic brands that uses brand ambassadors. This study aims to determine whether there is and influence and how much influence there is using a brand ambassador on the brand image of L'Oreal Paris. This research uses a quantitative methodology, with data collection techniques using a questionnaire. The results of data processing show that there is a significant influence of using a brand ambassador to brand image of L'Oreal Paris. The contribution of the effect of variable X (brand ambassador) to Y variable (brand image) is 38.2%, with a regression coefficient value of 0.615.